Energy-Efficient HVAC Systems: Enhancing Sustainability in Low-Income Housing - pandya, Brijesh (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
In the recent trend of developing sustainable societies aspiring to net-zero initiatives, the use of energyefficient HVAC systems has become increasingly popular, specifically in low-income housing schemes. Conventional designs (HVAC) are subjected to high levels of energy consumption exacerbating increased cost of utility and severe environmental damages. This paper aimed to explore innovative and energy-efficient HVAC designs that can significantly contribute to developing sustainable societies with a net-zero future while fostering the environment of social equity. By conducting a comprehensive review of the contextual literature and related studies, the research highlights the significance of energy-efficient HVAC systems in developing sustainable societies and the key challenges preventing the smooth adaptation of modern HVAC systems.